THE DEVELOPMENT OF ASEAN'S INTELLECTUAL PROPERTY RIGHTS LAW, FROM TRIPS COMPLIANCE TO HARMONIZATION - Barizah, Nurul (Indonesia Law Review, 2017)
Intellectual Property Rights (IPR) is one of the most important subjects of trading, not only in the era of globalism, but also in this era of regionalism. In the regional ASEAN, its significant of IPR protection has made Member Nations introduced ASEAN Framework Agreement on Intellectual Property (IP) Cooperation in 1995, a year after the conclusion of the Trade-related Aspects of Intellectual Property Rights (TRIPs) Agreement of the World Trade Organization (WTO). This paper discusses the current development of this Framework in the light to harmonise Intellectual Property (IP) laws in the region, covering the objectives, the basic principles, and some substantial provisions. Then, it examines whether fast pace of IP laws development in ASEAN have been mainly driven by this Framework Agreement or the countries’s deadline to comply with the TRIPs obligations. This paper also examines whether the regional economic cooperation of ASEAN Free Trade Agreement (FTA) with their trading partners pay a specific attention to the issue of IPR. By taking into account the different level of national IPRs laws, and its current development, it can be concluded that the ASEAN framework on IP Cooperation is rather ambitious. The Working Groups succeeded in developing draft on regional filing forms for IP registration, but the progress in the introduction of the system has been very slow.